INTERNALIZATION OF WASAṬIYYAH ISLAMIC VALUES THROUGH ISLAMIC RELIGIOUS EDUCATION LEARNING AT LAKSAMANA MARTADINATA PRIVATE JUNIOR HIGH SCHOOL IN MEDAN - Khairul Umam Nasution; Syamsu Nahar (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to describe the planning of Islamic Religious Education learning in internalizing the values of Islam wasaṭiyyah, examine the internalization process, and identify the supporting and inhibiting factors at SMP Swasta Laksamana Martadinata Medan. This study employed a qualitative approach with a case study design. Data were collected through observation, semi-structured interviews, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that the planning of Islamic Religious Education learning was conducted systematically by integrating the values of Islam wasaṭiyyah both implicitly and explicitly through learning objectives, materials, methods, media, and learning activities. The internalization process occurred through three stages, namely value transformation, value transaction, and value transinternalization. In the transformation stage, the values of Islam wasaṭiyyah were conveyed through material explanation, advice, and role modeling. In the transaction stage, these values were reinforced through discussions, deliberation, and group work. Furthermore, in the transinternalization stage, the values of Islam wasaṭiyyah were reflected in students’ daily behavior, such as mutual respect, tolerance, and cooperation. Supporting factors for the internalization process included an inclusive school culture, equal treatment policies toward students, and school programs based on togetherness. Meanwhile, the inhibiting factors included the influence of social media, parenting patterns of some parents that were not fully aligned with the values of Islam wasaṭiyyah, and limited instructional time for Islamic Religious Education learning.